Soviet National Income Accounts for 1955 - Bornstein, Morris (The Review of Economics and Statistics, 1962)
PpT HIS paper presents in very concise form the principal results of a detailed estimate of the national income and product of the Soviet Union in I955, together with a brief discussion of the problems involved in the construction of such accounts.' Although at least two other estimates of Soviet national income accounts for I955 by the Economic Commission for Europe (ECE) 2 and by Hoeffding and Nimitz3 are available, the study on which this paper is based differs from them in several respects.4 The ECE study, which follows the United Nations system of national accounts,5 presents basic sector accounts but does not contain enduse or origin breakdowns or an adjustment of established prices for indirect taxes and subsidies. The Hoeffding-Nimitz study, which uses the format devised by Professor Bergson following that of the United States Department of Commerce,6 does include an end-use breakdown in established prices, but it lacks a similar one in adjusted prices and also lacks an origin breakdown. In contrast, the study summarized in this paper contains both end-use and origin breakdowns at both established and adjusted prices.7 In addition, the results are presented in a form intended to facilitate comparisons (i) of the purchasing power of the ruble and foreign currencies in regard to national product (and its major components) and (2) of the relative size of Soviet national product (and its major components) and that of another country in a common currency for example, with United States national product through the use of appropriate ruble-dollar or dollar-ruble ratios.8 In the limited space available, this paper presents the basic accounts constructed in the underlying study, the resulting end-use and origin breakdowns at established and adjusted prices, and some observations on the problems and limitations involved in the construction of Western-style national accounts for Soviettype economies.